solve the equation and check your solution by substituting in the equation 3(x-3)=4(2x+4)
Answers
Answered by
3
Here is the answer
![\bf{3(x - 3) = 4(2x + 4)} \bf{3(x - 3) = 4(2x + 4)}](https://tex.z-dn.net/?f=+%5Cbf%7B3%28x+-+3%29+%3D+4%282x+%2B+4%29%7D)
![\bf{3x - 9 = 8x + 16} \bf{3x - 9 = 8x + 16}](https://tex.z-dn.net/?f=+%5Cbf%7B3x+-+9+%3D+8x+%2B+16%7D)
![\bf {- 9 - 16 = 8 - 3x} \bf {- 9 - 16 = 8 - 3x}](https://tex.z-dn.net/?f=+%5Cbf+%7B-+9+-+16+%3D+8+-+3x%7D)
![\bf{- 25 = 5x} \bf{- 25 = 5x}](https://tex.z-dn.net/?f=+%5Cbf%7B-+25+%3D+5x%7D)
![\bf{x = - 5} \bf{x = - 5}](https://tex.z-dn.net/?f=+%5Cbf%7Bx+%3D+-+5%7D)
The value of x is -5.
Thanks!!
#BeBrainly!!
The value of x is -5.
Thanks!!
#BeBrainly!!
Answered by
0
\bf{3(x - 3) = 4(2x + 4)}
\bf{3x - 9 = 8x + 16}
\bf {- 9 - 16 = 8 - 3x}
\bf{- 25 = 5x}
\bf{x = - 5}
The value of x is -5.
Similar questions
Hindi,
8 months ago
Social Sciences,
8 months ago
English,
8 months ago
Math,
1 year ago
Biology,
1 year ago